Effect of Growth Space on The Productivity of Maize Using Three Sisters Cultivation with Bee Pollination - Putri, Nadia Damika; Purqon, Acep; Putra, Ramadhani Eka (Jurnal Biodjati, 2023)
he increasing number of food needs is one of the driving factors for increasing agricultural production, but there are constraints on the availability of land. A polyculture system with corn, beans, and pumpkins, commonly known as the three sisters, can create positive interactions that can enhance the growth and development of each plant. This system has a vast potency to be applied to urban farming inside a grow bag because it does not require ample space, the placement of plants is flexible, and it produces a variety of yields. However, it is necessary to assess the effect of growing space on the growth of maize (Zea mays) cultivated by the three-sister system. This study used a completely randomized design with three treatments and six replications. The treatment consists of three planting spaces with various growing bags (treatment A:75 L, B:100 L, and C:200 L). The results of this study showed that the highest corn productivity was in the largest growing space (treatment C), which weighed 318.40 g/cob, and without husks 246.42 g/cob, but not significantly different from treatment B (grow bag 100 L), which weights 316.20 g/cob and without pods of 240.63 g/cob. This study found that the 100 L grow bag was the optimal growing space for planting corn in containers using the three sisters technique.